Estudos cariotípicos em citótipos de Handroanthus ochraceus e Handroanthus chrysotrichus (Bignoniaceae) - Matos, Angélica de Nazaré Silva (2015)
The Bignoniaceae family is pantropical and has about 827 species and 82 genera with the Handroanthus genus composed of woody species known popularly as ‘Ipê’. The yellow corolla and trichomes in the leaves and stem characterize these species. In the field there are problems with identification of Handroanthus ochraceus and Handroanthus chrysotrichus due to the presence of individuals with intermediate characteristics in the same area, as well as the report of successful artificial hybridization between these species, suggesting the possibility of natural hybridization, even though this is considered rare in Bignoniaceae. Chromosome counts and morphological characterization by banding with fluorochromes CMA / DAPI were performed in two species of Handroanthus with 9 individuals from different locations in order to investigate patterns of karyotypic evolution. None of the cytotypes showed DAPI+ bands, but CMA+ bands varied from 5 to 18. The individual of Três Marias was the only one to show conserved chromosome number (2n = 80) and also the same amount of CMA+ bands. The other cytotypes, both diploid and polyploid, showed different patterns of bands in the same individual, as well as chromosomal losses, which suggests that these individuals are in a process of karyotype evolution. In situ hybridization studies are suggested to confirm such inferences as well as the sampling of other populations.